New taxa of Impatiens (Balsaminaceae) from Madagascar VIII. Impatiens max-huberi, a new species from Marojejy and Anjanaharibe-Sud - Fischer, Eberhard; Rahelivololona, Marie Elisette (Phytotaxa, 2016)
The new species Impatiens max-huberi is described from Mt. Marojejy. It is resembles Impatiens sambiranensis from Northwestern Madagascar in the large pink-purple flowers with long spur, but differs in the alternate leaves and the curved spur.